PENGARUH GOOD CORPORATE GOVERNANCE DAN KOMPENSASI BONUS TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Desiana Putri Ikawati Manuhutu; Edi Joko Setyadi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
Earnings management is measure that can influence the reported earnings and function to benefit itself. Earnings management measure can be done by various strategy such as increasing income or profit. This research was aimed at analyzing to giving empirical evidences of the effect of Good Corporate Governance (managerial ownweship, institutional ownership, board of direction, audit committee) and bonus compensation towards the earnings management using proxcy as discretionary accrual. The samples of this research were manufacturer company in the goods and consumption industrial sector listed in Indonesia Stock Exchange from 2012 to 2014 used secondary data in a from of annual report and company’s financial report from Indonesia Stock Exchange. The data were analyzed through multiple linear regression. The result of this research showed that managerial possession did not negative effect the earnings management, institutional possession did not negative effect the earnings management, board of directions did not positive effect the earnings management, audit committee had negative effect the earnings management, and bonus compensation did not positive effect the earnings management.Keywoards: Managerial Possession, Institutional Possession, Board of Directions, Audit Committee, Bonus Compensation, Earnings Management